2020
DOI: 10.1017/dmp.2020.346
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Fatal Outcome in Patients With COVID-19 Pneumonia

Abstract: Aim: To correlate the clinical, laboratory, and radiographic characteristics of patients with a confirmed diagnosis of COVID-19 disease, with fatal outcome. Methods: We reviewed Chest X-Ray (CXR) features, clinical, and laboratory data of patients with RT-PCR confirmed diagnosis of COVID-19 infection. The relationship with mortality was investigated by fitting a logistic regression model. Results: 246 patients were included (170 males; mean age: 63). Most of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Before beginning any medical therapy for patients with COVID-19, evaluation of the seriousness of the disease by a chest X-ray (CXR) performed at hospital admission should be considered. Imaging examination is widely claimed to play a pivotal role in COVID-19 management [ 7 - 9 ]. Currently, there are some established CXR scoring systems for quantifying lung abnormalities, including the Brixia and Radiographic Assessment of Lung Edema (RALE) classifications.…”
Section: Introductionmentioning
confidence: 99%
“…Before beginning any medical therapy for patients with COVID-19, evaluation of the seriousness of the disease by a chest X-ray (CXR) performed at hospital admission should be considered. Imaging examination is widely claimed to play a pivotal role in COVID-19 management [ 7 - 9 ]. Currently, there are some established CXR scoring systems for quantifying lung abnormalities, including the Brixia and Radiographic Assessment of Lung Edema (RALE) classifications.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic intermittent hypoxia is a life-threatening condition that happens in many diseases and situations, including chronic obstructive pulmonary disease, congestive heart failure and obstructive sleep apnea syndrome, all of which may coexist with SARS-CoV-2 infection in some patients. [30] As previously discussed, hypoxemia can appear in early stages of COVID-19. Hypoxia is a common feature in infl ammatory sites, which can eventually result in hypoxemia, leading in turn to induction of factors like HIF-1α.…”
Section: Perspective Peer Reviewedmentioning
confidence: 87%
“…HIF-1α is activated during the immune response and plays an important role at the infl ammation site by inducing proinfl ammatory cytokine production, leading to CS. [10,20,[23][24][25]30] All the evidence connecting hypoxemia with CS highlights the importance of avoiding the former in COVID-19 patients as early as possible, to prevent development of the latter, by using noninvasive ventilation (NIV), as described in the following section.…”
Section: Perspective Peer Reviewedmentioning
confidence: 99%
“…Studies have shown chest radiographs of patients with DM to have increased bilateral airspace consolidation compared to patients without DM[ 12 , 13 ]. The severity of chest radiograph changes in patients with DM has indicated a significant correlation with mortality, as evidenced in multivariate analysis by Cellina et al [ 14 ]. Patients with bilateral peripheral alveolar disease (Figure 1 ) often present at a later stage and have a worse outcome.…”
Section: Literature Searchmentioning
confidence: 99%